Masked voices : gay men and lesbians in Cold War America - Loftin, Craig M. (SUNY series in queer politics and cultures., 2012)
"An analysis of unpublished letters to the first American gay magazine reveals the agency, adaptation, and resistance occurring in the gay community during the McCarthy era."--Publisher description